FEEDING PRACTICES IN THE FIRST YEAR OF LIFE: CHALLENGES TO FOOD AND NUTRITION POLICIES - Lorena dos Santos Tinôco; Clélia de Oliveira Lyra; Tamires Carneiro de Oliveira Mendes; Yan Nogueira Leite de Freitas; Adriana Souza da Silva; Ana Maria Silva Souza; Maria Ângela Fernandes Ferreira (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To evaluate the feeding practices for infants under one year of age, according to food and nutrition policies. Methods: This is a descriptive cross-sectional study based on secondary data from the Chamada Neonatal project (research on prenatal, childbirth, and infant care) in the state of Rio Grande do Norte. The sample analyzed comprised 837 mother/child (under one year of age) pairs. We found a prevalence of data on exclusive breastfeeding (EBF) in the first hour of life - partial and total -, as well as on food consumed by children 24 hours prior to the interview. We estimated the probability of consumption according to the child's age in days using the probit analysis. Results: Among the interviewed mothers, 64.8% (95%CI 62.4-70.8) declared breastfeeding in the first hour of life, and 60% (95%CI 56.41-63.07) of the children were still breastfed at the end of their first year of life. The median duration of EBF was 63 days (95%CI 60-67). Water or tea, dairy products, fruits, and vegetables were introduced early, with medians lower than 180 days. The probit analysis revealed that the consumption of breast milk tended to decrease and food intake to increase as the child gets older, with exponential growth in the "unhealthy food" group. Conclusions: Although most children were breastfed up to one year of life, few did so exclusively. Foods were introduced early, with increased consumption of unhealthy ones, resulting in inadequate dietary quality according to recommendations from food and nutrition public policies.